CYBERCRIME EXPERIENCE'S IMPACT ON WOMEN'S EMOTIONS: A CASE STUDY IN PENANG - Mat Ghani, Norhayati; Abu Bakar, Mohd Azmeer; Rosli, Hafizah (Malaysian Journal of Tropical Geography (MJTG), 2023)
According to reports, 73% of women worldwide are cybercrime victims due to the consumption of social media. Cybercrime incidents have various effects on female victims, including emotional, relationship, and educational consequences. This study aims to investigate the emotional effects of cybercrime among the female victims. Ten women who were victims of cybercrime were selected for in-depth interviews using snowball and purposive sampling. This study employed the qualitative approach; the data was analyzed using content analysis. The results show that cybercrime involving instances of cyberbullying and fraud was the most prevalent among respondents, at 21.4%. The emotional effects of cyberbullying and fraud include sadness, trauma, embarrassment, stress, depression, frequent crying, anxiety, distraction, anger, fear, depression, loss of trust, always thinking negatively, lack of self-confidence, and becoming a hater. This study provides information about the emotional impact of cybercrime on women who use social media. This study suggested that government agencies and related organizations should consider the potential dangers posed by social media, which could negatively impact the emotional and psychological health of young women.